Adhesion of marine fouling organisms on hydrophilic and amphiphilic polysaccharides - Bauer, Stella; Arpa Sancet, Maria Pilar; Finlay, John A.; Callow, Maureen E.; Callow, James A.; Rosenhahn, Axel (Langmuir, 2013)
Polysaccharides are a promising material for nonfouling surfaces because their chemical composition makes them highly hydrophilic and able to form water-storing hydrogels. Here we investigated the nonfouling properties of hyaluronic acid (HA) and chondroitin sulfate (CS) against marine fouling organisms. Additionally, the free carboxyl groups of HA and CS were postmodified with the hydrophobic trifluoroethylamine (TFEA) to block free carboxyl groups and render the surfaces amphiphilic. All coatings were tested with respect to their protein resistance and against settlement and adhesion of different marine fouling species. Both the settlement and adhesion strength of a marine bacterium (Cobetia marina), zoospores of the seaweed Ulva linza, and cells of a diatom (Navicula incerta) were reduced compared to glass control surfaces. In most cases, TFEA capping increased or maintained the performance of the HA coatings, whereas for the very well performing CS coatings the antifouling performance was reduced after capping.